Multimedia prototype of a Bilingual Model within technology based learning environment: An implementation of a mathematics learning framework - Dahlan, Zuraini; Shafie, Noraimi; Rashid, Rozeha A. (2006)
In response to the current globalization in the educational arena, and to the new policy of change in the medium of instruction for teaching mathematics and science in English as implemented by the Malaysian Government in 2003, we introduce the e-learning Bilingual Model which has been designed and used at the university. The multimedia prototype of the model consists of text-based content for first-year mathematics subjects with exact forms available in both the English language and the native language. Content is identified to provide descriptions of core concepts dynamically using, audio, video and graphics, and also constructed to provide bilingual glossaries. The combination of Information Communication Technologies (ICT) such as Short Messaging Service (SMS), MOODLE e-learning, and Freeware Online-portals for Group-websites (FrOG) become the setting for an integrated framework for Technology Based Learning Environment, and work as instructional delivery tools in addition to the traditional method of teaching mathematics.